Exploring the Peer Tutor Experiential Learning Process: New NSSE research suggests the high impact of peer tutoring. - Cole, James; Keller, Page; Kinzie, Jillian; Kuh, George (Experiential Learning and Teaching in Higher Education, 2024)
While peer tutoring is a valued experiential activity, little is known about the peer tutoring experience and its relationship to desired 21st century outcomes of college. This paper features the results from a multi-institution study of the characteristics and benefits of peer tutoring for tutors. The National Survey of Student Engagement was administered along with a set of experimental questions specifically designed to interrogate the process of peer tutoring at 30 four-year institutions. In general, peer tutors who identified as seniors in college showed patterns of engagement and gains in learning and personal development that exceeded substantially those of their non-tutor counterparts, especially for those who received training and feedback from supervisors. The findings have implications for tutoring program administrators, experiential educators, and others to enhance the effects of peer tutoring and other experiential learning activities.